An analysis of the South African tax policy on hybrid debt instruments with reference to international developments - Essop, Hasinah (My University, 2016)
The popularity of hybrid instruments as a tax planning technique has grown over the years. There is an increasing global awareness on the use of these instruments and on addressing the tax gaps created by these instruments. South Africa introduced significant amendments to the legislation on hybrid debt instruments, ahead of many countries around the globe. This research report examines hybrid debt instruments and the tax concerns which have created the need for specific tax legislation addressing such instruments. It considers tax policies proposed by the international tax fraternity, global trends in changes to tax policies and South Africa‘s stance on such tax policies. The amended section 8F and new section 8FA of the Income Tax Act are included in this consideration. Key words: arrangement, debt, deductible, dividend, equity, host country, interest, hybrid debt instrument, hybrid interest, home country, tax
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation)
Keywords: Taxation--Law and legislation--South Africa; International business enterprises--Taxation--Law and legislation; Debt financing (Corporations)--South Africa